Possibilities in Germ Cell Research: An Engineering Insight. Issue 12 (December 2015) - Esfandiari, Fereshteh; Mashinchian, Omid; Ashtiani, Mohammad Kazemi; Ghanian, Mohammad Hossein; Hayashi, Katsuhiko; Saei, Amir Ata; Mahmoudi, Morteza; Baharvand, Hossein
Abstract : Germ cells (GCs) are responsible for fertility and disruptions in their development or function cause infertility. However, current knowledge about the diverse mechanisms involved in GC development and function is still in its infancy. This is mainly because there are low numbers of GCs, especially during embryonic development. A deeper understanding of GCs would enhance our ability to produce them from stem cells. In addition, such information would enable the production of healthy gametes for infertile couples. In this regard, pluripotent stem cells (PSCs) demonstrated a promising ability to produce GCs in vitro . In this review, we highlight recent advances in the field of tissue engineering that suggest novel strategies to enhance GC research. Trends: Advanced therapies for infertility require developing systems for the efficient production of germ cells from stem cells in the laboratory. We discuss recent advances and challenges of germ cell research. Here, we propose engineering approaches for designing an artificial niche for germ cell development in vitro . Novel platforms are demonstrated for the epigenetic analysis of germ cells. Innovative approaches are detailed for the efficient production of germ cells from pluripotent stem cells.